1979
DOI: 10.1111/j.1476-5381.1979.tb07870.x
|View full text |Cite
|
Sign up to set email alerts
|

Shape Change of Blood Platelets—a Model for Cerebral 5‐hydroxytryptamine Receptors?

Abstract: In blood platelets of rabbits isolated by a stractan gradient and incubated in a protein‐poor medium, tryptamine, 5‐hydroxytryptamine (5‐HT) and derivatives, quipazine and mescaline caused a shape change. This shape change was inhibited by low concentrations of methysergide. The most potent antagonists of the 5‐HT‐induced shape change included ergoline derivatives and neuroleptic drugs, which showed high stereoselectivity. (‐f)‐Lysergic acid diethylamide ((+)‐LSD), psilocine and some N',N′‐dimethylated tryptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…However, this increase was rather slow (maximum attained after 30 min) and was only seen in the presence of extracellular Ca2+ (Affoter et al, 1984). In contrast, the 5-HT-induced shape change reaction is a rapid event which also occurs in a Ca2+-poor medium containing disodium edetate (EDTA) (Born et at., 1978;Graf & Pletscher, 1979;Affolter et al, 1984). Using a slightly modified quin-2-method we have shown in the present experiments that in platelets, stimulation of the 5-HT2-receptor causes an elevation of intracellular free Ca2+ as rapid as the shape change reaction, even in a Ca2+-poor medium.…”
Section: Introduction Methodssupporting
confidence: 47%
“…However, this increase was rather slow (maximum attained after 30 min) and was only seen in the presence of extracellular Ca2+ (Affoter et al, 1984). In contrast, the 5-HT-induced shape change reaction is a rapid event which also occurs in a Ca2+-poor medium containing disodium edetate (EDTA) (Born et at., 1978;Graf & Pletscher, 1979;Affolter et al, 1984). Using a slightly modified quin-2-method we have shown in the present experiments that in platelets, stimulation of the 5-HT2-receptor causes an elevation of intracellular free Ca2+ as rapid as the shape change reaction, even in a Ca2+-poor medium.…”
Section: Introduction Methodssupporting
confidence: 47%
“…Other 5-HT receptors are mediated by adenylyl cyclase [23,46] or ion channels or the mediating effector system is still unknown. Graf and Pletscher [20] found that the 5-HT receptor of platelets resembles that of nerve cells. Further studies characterized the 5-HT 2A receptor binding in platelets [18,38,43] .…”
mentioning
confidence: 98%
“…Among several other similarities, it has been demonstrated that the platelet's release reaction is physiologically equivalent to the synaptosome's secretion of neurotransmitters (Stormorken, 1969). In addition, both preparations share common agonists and receptor properties (Boullin & Glenton, 1978;Graf & Pletscher, 1979;Brodde, et al, 1983).…”
Section: Introductionmentioning
confidence: 99%